Microscale structural changes of individual fibrin fibers during fibrinolysis - Lynch, Spencer R.; Laverty, Sean M.; Bannish, Brittany E.; Hudson, Nathan E. (My University, 2022)
Fibrinolysis is the enzymatic digestion of fibrin, the primary structural component in blood clots. Mechanisms of fibrin fiber digestion during lysis have long been debated and obtaining detailed structural knowledge of these processes is important for developing effective clinical approaches to treat ischemic stroke and pulmonary embolism. Using dynamic fluorescence microscopy, we studied the time-resolved digestion of individual fibrin fibers by the fibrinolytic enzyme plasmin. We found that plasmin molecules digest fibers along their entire lengths, but that the rates of digestion are non-uniform, resulting in cleavage at a single location along the fiber. Using mathematical modeling we estimated the rate of plasmin arrival at the fiber surface and the number of digestion sites on a fiber. We also investigated correlations between local fiber digestion rates, cleavage sites, and fiber properties such as initial thickness. Finally, we uncovered a previously unknown tension-dependent mechanism that pulls fibers apart during digestion. Taken together these results promote a paradigm shift in understanding mechanisms of fibrinolysis and underscore the need to consider fibrin tension when assessing fibrinolytic approaches.
Keywords: Fibrinogen; Hemostasis; Microscopy; Modeling; Plasmin